POTENSI MIKROORGANISME SEBAGAI AGEN BIOREMIDIASI DALAM MENURUNKAN KADAR Cr (vi) DALAM LIMBAH CAIR TEKSTIL HASIL PEWARNAAN - Umi Fatmawati; Sajidan Sajidan; Suranto Suranto (Universitas Sebelas Maret, 2010)
ABSTRACT Hexavalent chrom (Cr(VI)) is recognized as toxic heavy metal, produced from textile printing manufacture. Negatif effect of Cr(VI) shuold be reduced towards biotic environtment, so it is important to reduce Cr(VI) become Cr(III) which little hazard. Pseudomonas aeruginosa, Pseudomonas putida, Klebsiella pneumonia, Pantoea sp and Saccharomyces cerevisieae. They are including as resistent Cr(VI) microorganism and they have ability to reduce Cr(VI). The aim of the research is to know the ability of microorganism in reducing Cr(VI) and knowing protein band pattern between Cr(VI) resistent microorganism and microorganism which is inoculated on LB broth without Cr(VI). Electrophoresis SDS-PAGE is the methode which is used to indentified protein expression. While, for knowing concentration Cr(VI) in liquid medium is used by 1,5 difenilkarbazid methode. The quantitative data is obtained being analyzed by ANAVA two factorial continued with Duncan test at 1% level test. The qualitative data include protein expression analyzed by Relative mobility (Rf) and for knowing molecular weight of protein is used protein marker. The qualitative data had been analyzed by descriptive qualitative methode.The result of the research shows that in Cr(VI) concentration after being treat by the microorganisms at the initial concentration 0, 5ppm, 1 ppm, 5 ppm and 10 ppm and compared the reduce Cr(VI) capability from the average procentage data each microorganism are: P. putida (65%) > S. cerevisieae (64,45%) > P. aeruginosa (60,73%) > Pantoea sp (50,22%) > K. pneumonia (47,82%) > without microorganism (34,25%). The adding microorganisms have influence toward reduction of Cr(VI). Key word: Cr heavy metal, microorganism, protein, electrophoresis